Implementasi Kebijakan Publik dalam Penegakan Hukum Lingkungan terhadap Praktik Pembalakan Liar di Indonesia (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
Air quality in the Special Capital Region of Jakarta has shown a concerning decline in recent years, largely due to high emissions from motor vehicles as the main source of pollution in urban areas. The Provincial Government of DKI Jakarta issued Governor Regulation Number 66 of 2020 concerning Exhaust Emission Testing for Motor Vehicles as a public policy instrument aimed at controlling air pollution. This study aims to analyze the implementation of the regulation from a public policy perspective and to identify supporting and inhibiting factors in its execution. The research employs a normative juridical method with statutory and conceptual approaches, supported by qualitative analysis of policy documents and reports on the implementation of emission testing. The results reveal that the implementation of the regulation has not been optimal due to limited emission testing infrastructure, low levels of public awareness and socialization, and inconsistent enforcement of administrative sanctions. Nevertheless, there are opportunities to improve policy effectiveness through strengthened inter-agency coordination, digitalization of monitoring systems, and increased environmental literacy among the public. Therefore, the success of emission control policy implementation is highly dependent on resource support, regulatory consistency, and community awareness, necessitating a comprehensive and continuous multi-stakeholder improvement strategy and stronger commitment.